Analysis of the Improvement of Students' Cognitive Ability in Science Subjects Using the Think-Pair-Share Learning Model at SMP Negeri 2 Gunungsitoli - Hulu, Debi Rebeka; Lase, Natalia Kristiani; Zega, Novelina Andriani; Gulo, Hardikupatu (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The ability to understand science concepts is very important for everyone to have a greater opportunity to adapt in life, especially in terms of mastering reading skills to improve the development of a country. The purpose of this study was to determine the effectiveness of the think-pair-share learning model in improving students' cognitive abilities during the science learning process. This research is a quasi-experimental research with matching pretest-posttest control group design conducted at SMP Negeri 2 Gunungsitoli. The average result of cognitive ability in the experimental class was 82.20 which was in the very good category, while the average cognitive ability of students in the experimental class was 68.80 which only increased to a sufficient category. The N-gain result in the control group was 0.36 which was in the moderate category, while the N-gain in the control group was 0.79 which was in the moderate category. After the application of the think-pair-share learning model, it was concluded that the cognitive level of students increased to the C4-analyze level. This research provides an alternative science learning model that is more varied so that science teachers can apply it to the classroom.